2008
DOI: 10.1002/ejic.200800572
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Density Functional Theory Studies on the Crystal Structures and Magnetic Properties of Mg(Mg1–xMnx)2Sb2 (x ≈ 0.25) and BaMn2Sb2

Abstract: Reported are the synthesis and structural characterization of two ternary transition metal intermetallic compounds, Mg(Mg1–xMnx)2Sb2 (where x is approximately 0.25) and BaMn2Sb2·Mg(Mg2.50(3)Mn0.5)2Sb2 crystallizes in the trigonal space group P$\bar {3}$m1 (no. 164) and belongs to the CaAl2Si2‐type, while BaMn2Sb2 is isostructural with the body‐centred tetragonal ThCr2Si2‐type (I4/mmm, no. 139). Both structures have been refined from single‐crystal X‐ray diffraction data and their magnetic properties determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 45 publications
6
36
1
Order By: Relevance
“…The 2D-curvature is an improved version of the laplacian to track dispersive features in image plots, which is based on the Gauss theory of curvature. We observe two hole bands at the BZ center, none of them crossing E F , as expected from the antiferromagnetic ground state and semiconducting behavior of BaMn 2 As 2 [9,14,15]. While the inner hole band is gapped by about 200 meV below E F for both k z values, the band gap of the outer one varies from nearly 93 to 300 meV between Γ and Z.…”
Section: Resultssupporting
confidence: 64%
“…The 2D-curvature is an improved version of the laplacian to track dispersive features in image plots, which is based on the Gauss theory of curvature. We observe two hole bands at the BZ center, none of them crossing E F , as expected from the antiferromagnetic ground state and semiconducting behavior of BaMn 2 As 2 [9,14,15]. While the inner hole band is gapped by about 200 meV below E F for both k z values, the band gap of the outer one varies from nearly 93 to 300 meV between Γ and Z.…”
Section: Resultssupporting
confidence: 64%
“…17 We find that the Mn compounds are rather different from the Fe, Co and Ni compounds in that there is much stronger hybridization with the pnictogen p states. This leads to an electronic structure that cannot be regarded as derived from that of the Fe compound with a different electron count.…”
Section: Theoretical Methodsmentioning
confidence: 67%
“…2, 17 We note that BaMn 2 Sb 2 , BaMn 2 As 2 and BaFe 2 As 2 are composed of common, inexpensive elements, which as mentioned is an important consideration for some thermoelectric ap-plications. Key questions concern the relationship between BaMn 2 As 2 and BaMn 2 Sb 2 , and that between the Mn and Fe compounds, as well as the related issue of whether the conductivity in the Mn compounds can be improved by doping, while at the same time maintaining high thermopowers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous theoretical electronic structure studies on BaMn 2 Sb 2 suggested a G-type AFM ordering [61,62], but T N and the AFM structure have not been experimentally determined. Transport measurements revealed that BaMn 2 Sb 2 has a room-temperature Seebeck coefficient of ∼225 μV/K, consistent with semiconducting behavior.…”
Section: Introductionmentioning
confidence: 91%